ENHANCEMENT AND INTEGRATION OF OPTICAL SATELLITE IMAGES WITH SRTM DATA FOR MAPPING AND STUDY OF LARGE FLUVIAL PLAINS: EXAMPLES IN THE BRAZILIAN PANTANAL - Merino, Eder Renato [UNESP]; Pupim, Fabiano do Nascimento [UNESP]; Macedo, Hudson de Azevedo [UNESP]; Assine, Mario Luis [UNESP] (Uniao Geomorfologia Brasileira, 2015)
Studies concerning the physiography and function of fluvial systems have increased both Worldwide and in the large Brazilian fluvial systems. These areas are difficult to study due to problems concerning accessibility and mobility. Remote sensing and geotechnologies are alternatives to partially overcome those difficulties. Digital elevation models (DEMs) have become the most common methods for analyzing and extracting topographic information and the SRTM (Shuttle Radar Topography Mission) provides the most complete global DEM. However, in seasonally flooded areas and large fluvial plains, much of the spatial information is omitted due to lack of adequate processing of the DEM. This paper presents techniques for the enhancement of SRTM data applied to geomorphological studies in large fluvial plains using the Brazilian Pantanal as an example. After being properly processed, according to the relief and morphological characteristics, SRTM data highlighted major distributary fluvial systems (megafans) and its internal characteristics (channel levees and distributary lobes). IHS fusion (Intensity-Hue-Saturation) of composition R7G4B3 (Landsat 7 ETM+) and shaded-relief image derived from SRTM TOPODATA (Hillshade) highlighted the boundary between the Pantanal and metamorphic rocks of the basement. This paper demonstrates that even in extremely flat areas like the Pantanal, additional processing improves significantly the identification of morphological characteristics captured by SRTM data.
Keywords: SRTM; Pantanal; Remote Sensing; Fluvial Systems